2020
DOI: 10.3390/cancers12103073
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mutational Landscape and Tumor Immune-Microenvironment in Liver Oligo-Metastatic Colorectal Cancer

Abstract: Genetic dynamics underlying cancer progression are largely unknown and several genes involved in highly prevalent illnesses (e.g., hypertension, obesity, and diabetes) strongly concur to cancer phenotype heterogeneity. To study genotype-phenotype relationships contributing to the mutational evolution of colorectal cancer (CRC) with a focus on liver metastases, we performed genome profiling on tumor tissues of CRC patients with liver metastatic disease and no co-morbidities. We studied 523 cancer-related genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…Multivariate analysis showed that both mutational trajectories had an independent and significant prognostic power. As in our previous studies ( 5 , 6 ), we cannot definitively demonstrate if this effect depends on a negative immunologic selection ( 12 ) or on a spontaneous genetic devolution. Our translational studies are in progress to identify and isolate, from oligo-metastatic CRC patients, eventual T-cells responsible of mut KRAS clones’ elimination.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Multivariate analysis showed that both mutational trajectories had an independent and significant prognostic power. As in our previous studies ( 5 , 6 ), we cannot definitively demonstrate if this effect depends on a negative immunologic selection ( 12 ) or on a spontaneous genetic devolution. Our translational studies are in progress to identify and isolate, from oligo-metastatic CRC patients, eventual T-cells responsible of mut KRAS clones’ elimination.…”
Section: Discussioncontrasting
confidence: 74%
“…In fact, it is now clear that mCRC patients bearing specific KRAS (Kirsten RAt Sarcoma viral oncogene homolog) mutations do not benefit from anti-EGFR treatment because mutated and constitutively hyper-activated KRAS determine a ligand-independent activation of EGFR ( 4 ). We previously reported that loss of KRAS mutations (“regressive” mutational trajectories) from primary tumors to metastases on FFPE (Formalin-Fixed Paraffin Embedded) resected tissues was associated with long-term survivals and the oligo-metastatic status in mCRC ( 5 , 6 ). However, the evaluation of circulating tumor DNA (ctDNA) sequences, also called “liquid biopsy”, has provided a great opportunity to study the mutational evolution of cancers with a non-invasive, real-time and repeatable approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that the less adapted tumour microenvironment of the metastatic sites recruits more host immune cells attracted by the unidentified cancer cells than that of the primary tumour site. Recently, specific changes in cancer-related genes and immune cell infiltration in CRC metastases have been related to metastatic evolution, which produce new perspectives for cancer diagnostics and therapeutic strategies [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the gene mutation information in this study was derived from the primary tumor, not the metastatic sites. Considering the genetic evolution and alterations from primary to matched metastatic tissues ( 52 , 53 ), it is interesting to investigate the association between gene mutation in metastatic tissues and CRLM recurrence in the future.…”
Section: Discussionmentioning
confidence: 99%